Freedom without Justice the Prison Memoirs of Chol Soo Lee - Lee, Chol Soo 1952-2014 (University of Hawaii Press, 2018)
Freedom without Justice is a compelling story of ex-inmate Chol Soo Lee’s wrongful incarceration and the actions he took to survive years in prison, while political activists fought to win his retrial and freedom. It is at once a captivating chronicle of his life, a trenchant description of how prisons produce the very behaviors they purport to punish and prevent, and a poignant remembrance of an important chapter in Asian American history following the passage of the 1965 Immigration Act. At the age of twelve, Chol Soo immigrated to the United States from South Korea to reunite with his mother, who had arrived earlier as a military bride. In less than a decade, Chol Soo finds himself labeled as a violent criminal, convicted, and incarcerated for murder. His case quickly became a rallying point for an extraordinary pan–Asian American movement in the late 1970s and early 1980s, bringing together foreign- and American-born Asians in a common cause of justice and freedom.